The Cannabinoid CB1/CB2 Agonist WIN55212.2 Promotes Oligodendrocyte Differentiation In Vitro and Neuroprotection During the Cuprizone‐Induced Central Nervous System Demyelination. (4th February 2016) - Tomas‐Roig, Jordi; Wirths, Oliver; Salinas‐Riester, Gabriela; Havemann‐Reinecke, Ursula
Summary: Aim and methods: Different types of insults to the CNS lead to axon demyelination. Remyelination occurs when the CNS attempts to recover from myelin loss and requires the activation of oligodendrocyte precursor cells. With the rationale that CB1 receptor is expressed in oligodendrocytes and marijuana consumption alters CNS myelination, we study the effects of the cannabinoid agonist WIN55212.2 in (1) an in vitro model of oligodendrocyte differentiation and (2) the cuprizone model for demyelination. Results: The synthetic cannabinoid agonist WIN55212.2 at 1  μ M increased the myelin basic protein mRNA and protein expression in vitro . During cuprizone‐induced acute demyelination, the administration of 0.5 mg/kg WIN55212.2 confers more myelinated axons, increased the expression of retinoid X receptor alpha, and declined nogo receptor expression. Controversially, 1 mg/kg of the drug increased the number of demyelinated axons and reduced the expression of nerve growth factor inducible, calreticulin and myelin‐related genes coupling specifically with a decrease in 2′, 3′‐cyclic nucleotide 3′ phosphodiesterase expression. Conclusion: The cannabinoid agonist WIN55212.2 promotes oligodendrocyte differentiation in vitro . Moreover, 0.5 mg/kg of the drug confers neuroprotection during cuprizone‐induced demyelination, while 1 mg/kg aggravates the demyelination process.